Factors related to post-treatment chronic pain in breast cancer survivors: the interference of pain with life functions - (:unkn) unknown (My University, 2006)
The frequency and the intensity of chronic pain, as well as the related factors, were assessed in a cohort of breast cancer patients. The life functions were also questioned in patients who have post-treatment chronic pain. The scope of this retrospective study was a cohort of surgically-treated breast cancer patients with unilateral early stage disease who were under regular follow-up. Patients were eligible if they completed their treatments at least 6 months before and were free of disease. Patients who had a previous history of chronic pain syndrome, chronic debilitating disease, psychiatric diagnosis, and other cancers were excluded. All data regarding their demographics and treatments were recorded. Chronic pain was defined as the pain at treatment-related regions for a duration of at least three months after completion of treatment. Turkish version of "Brief Pain Inventory (Short Form)" was given to the patients with chronic pain in order to assess their pain intensity and life functions. The factors related to chronic pain were compared between patients with and without chronic pain. Eighty-five eligible female patients were included in the study. Thirty-nine (46%) patients declared that they had chronic pain. The mean VAS scale score was 4.1 +/- 2.4 cm in these patients. The mean age of patients with chronic pain (54.3 +/- 12.6 years) was significantly less than that of the ones without pain (60.4 +/- 13.6 years; p = 0.035). Radiotherapy was found to be significantly related to chronic pain (p=0.049; OR: 2.60; 95% CI 1.07-6.30). The VAS scores were 1.5 +/- 2.7 cm, 1.9 +/- 3.2 cm, 1.3 +/- 2.7 cm, 0.9 +/- 2.5 cm for general activity, mood, relations with other people, and sleep, respectively. Although almost half of the early stage breast cancer patients experienced post-treatment chronic pain, they rated the intensity of their pain as mild to moderate. Younger age and receiving radiotherapy were found to be significant contributing factors. The interference of post-treatment chronic pain with life functions was small. Overall, mood was found to be the most affected life function among all.
Keywords: Adult; Female; Humans; Middle Aged; Surveys and Questionnaires; Quality of Life; Aged; Aged, 80 and over; Follow-Up Studies; Retrospective Studies; Pain, Postoperative; Antineoplastic Agents; Pain Measurement; Breast Neoplasms; Activities of Daily Living; Women's Health; Radiotherapy, Adjuvant; Survivors; Mastectomy, Segmental